2019
DOI: 10.1021/acsnano.9b02621
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility, Wet-Transferred Graphene Grown by Chemical Vapor Deposition

Abstract: ‡) equal contributionWe report high room-temperature mobility in single layer graphene grown by Chemical Vapor Deposition (CVD) after wet transfer on SiO2 and hexagonal boron nitride (hBN) encapsulation. By removing contaminations trapped at the interfaces between single-crystal graphene and hBN, we achieve mobilities up to∼ 70000cm 2 V −1 s −1 at room temperature and∼ 120000cm 2 V −1 s −1 at 9K. These are over twice those of previous wet transferred graphene and comparable to samples prepared by dry transfer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
148
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 160 publications
(160 citation statements)
references
References 78 publications
9
148
1
2
Order By: Relevance
“…This n* is lower than in samples encapsulated using technologies compatible with wafer-scale processing, such as atomic layer deposition (ALD) (∼2.3 × 10 11 cm –2 46 and ∼3 × 10 11 cm –2 38 ) and is approaching those reported for exfoliated or CVD-based SLG/hBN heterostructures. 44 , 45 , 47 , 48 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This n* is lower than in samples encapsulated using technologies compatible with wafer-scale processing, such as atomic layer deposition (ALD) (∼2.3 × 10 11 cm –2 46 and ∼3 × 10 11 cm –2 38 ) and is approaching those reported for exfoliated or CVD-based SLG/hBN heterostructures. 44 , 45 , 47 , 48 …”
Section: Resultsmentioning
confidence: 99%
“…These values indicate a variation of both doping and strain within the mapped area, comparable to that of polycrystalline CVD-SLG encapsulated with hBN. 48 The presence (or coexistence) of biaxial strain cannot be ruled out. For uniaxial(biaxial) strain, Pos(G) shifts by ΔPos(G)/Δε ∼ 23(60) cm –1 /%.…”
Section: Resultsmentioning
confidence: 99%
“…36 When coupled with optimized transfer and interface cleaning, CVD-grown material, as used in this Article, has been shown to have as high a mobility as "pristine" exfoliated flakes. 37 We would speculate that the most likely origin of intrinsic defects is due to standard wet-transfer methods, as used here. Because defects within an otherwise impenetrable membrane provide the only pathway for charge to flow 38 further characterization of the inherent defects is important.…”
Section: Acs Nanomentioning
confidence: 93%
“…Less stringent experimental conditions are the dominant trend to the growth of graphene with simple transfer process and low‐temperature growth on arbitrary surfaces significant to reduce energy consumption. Fazio et al 49 reported the single‐layer graphene prepared by CVD and wet transfer on Si/SiO 2 substrate, which was subsequently encapsulated in hexagonal boron nitride. The high mobilities up to 70 000 cm 2 V −1 s −1 at room temperature and greater than 120 000 cm 2 V −1 s −1 at 9 K are achieved via combined encapsulation and interface cleaning.…”
Section: Synthesis and Structures Of 2d Group‐iv Materialsmentioning
confidence: 99%